Optimalisasi Pemanfaatan Lingkungan Sekitar Sebagai Media dan Sumber Belajar Bagi Anak Usia Dini Pada Masa Pandemi - Andi Aslindah; Desmiati Lawing (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
Learning resources are an inseparable part of children's learning activities and are very helpful in child development. The environment that surrounds us is one source that can be used to support learning activities optimally. Learning that makes the environment an object of learning can provide real and direct experience to students, especially for early childhood who still think from concrete things. The teacher's role is to plan children's learning activities and recommend media and learning resources that can be used. Then it is carried out by the children, accompanied by their parents as facilitators and motivators. Armed with creativity, parents can take advantage of the environment as a source of learning; no need to go to buy expensively, the environment adjacent to the house can be optimized to become a learning resource that is very valuable for the learning interests of students.